Veronica Enterprise Oil Palm Plantation Worker Management System - Sandrah, Eshra Novera; Zainal, Nurezayana (Applied Information Technology And Computer Science, 2026)
The Veronica Enterprise Oil Palm Plantation Worker Management System is a web-based application developed to improve the efficiency of managing plantation workforce operations. This project aims to resolve existing challenges caused by manual methods, such as delays in task assignment, inaccurate attendance records, and lack of real-time monitoring. The objectives of this project are to design the system using an object-oriented approach, to develop a comprehensive web-based platform for managing worker information and daily activities, and to test the system's functionality and usability through alpha and beta testing phases. The system will use a web-based approach, integrating Quick Response (QR) code technology for attendance tracking, task scheduling modules, and real-time activity monitoring, combined with report generation and staff management features. The prototyping methodology will be applied throughout the development process, enabling continuous refinement based on user feedback. Through this system, Veronica Enterprise is expected to improve task organization, reduce manual workload, and gain better insights for decision-making based on accurate and centralized data.